TECHNOLOGICAL CHARACTERIZATION OF Mezilaurus itauba WOOD: APPLICATION AND MACHINING TESTS - Rodrigues, Jaime Vieira; Barbosa, Felipe Manzoni; Dreyer, Jaqueline Beatriz Brixner; Schorr, Luís Paulo Baldissera; Cuchi, Tarik; Schlickmann, Monique Bohora (Floresta, 2020)
Brazil has several forest species that can be used for sustainable wood production. However, finding materials with technological quality is still a challenge. Wood is an excellent building material, however, there are few studies that have investigated the technological characterization, machining and processing of these species, including Mezilaurus itauba (Meisn.) Taub. Ex Mez. Thus, this study aimed to evaluate the technical characteristics and application potential of M. itauba wood from two distinct commercial lots, by analyzing its mechanical properties and performing machining tests. For this, static bending, dynamics and machining tests were carried out. The perpendicular compression tests of the evaluated fibers presented mean values of 9899.77 Mpa and 10670.74 Mpa for the elasticity module of lot 1 and lot 2, respectively. The average value observed for the L1 rupture module was 96.02 Mpa, while for L2 it was 113.85 Mpa. For the shear tests, low variation was observed between the specimens as well as between the evaluated lots. As for machining tests, M. itauba wood was classified as excellent for manufacturing furniture and internal openings. The M. itauba lots have acceptable mechanical strength, and the density is indicated for structural works, as well as for manufacturing furniture and interiors.